MANAGEMENT DAN TATA KELOLA AUDIT SISTEM INFORMASI - Laksamana Rajendran Haidar; Candra Supriadi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract The function in the development of information technology in human activities today is indeed developing very rapidly. Information empowerment technology has become a major facility in business activities. In information technology in the part of business contributes greatly to fundamental changes to structural, operational and organizational management. Human resources has provide a large influence in the management of information systems in an information technology organization that develops significantly, it also results in important changes in accounting and financial governance. The function of Information Technology in the development of financial bookkeeping in each part varies. Rapid of development of information systems is in line with the rate of development of financial accounting. In terms of internal control, data processing and improving the quality and quality of information, it is very influential in the development of information technology. Computer-based Accounting Information Systems in generating financial information also affect the audit process. The development of information systems that ultimately provide new opportunities as the auditor